Dampak Konglomerasi Media Terhadap Industri Media Massa dan Demokrasi Ekonomi Politik di Era Konvergensi Media - Khumairoh, Umi (Muqoddima: Jurnal Pemikiran dan Riset Sosiologi, 2021)
This study discuss about conglomeration media in convergence media era. The object of this research is how the impact of conglomeration media on politic economy democracy in Indonesia. In addition, this study also explain how the impact of media convergence on the mass media industry today. This research method uses a descriptive qualitative with literature studies approach and data collection through secondary data obtained through literature studies such as reference book, journals, articles and other sources related to research. This study concludes that media convergence involves many technological factors. Supported by the presence of the internet, it supports the application of media convergence that unites several media such as online media, e-paper, e-books, radio streaming, and social media.